The interaction of drought and habitat explain space–time patterns of establishment in saguaro (Carnegiea gigantea). Issue 3 (23rd January 2018) - Winkler, Daniel E.; Conver, Joshua L.; Huxman, Travis E.; Swann, Don E.
Abstract: The long‐lived columnar saguaro cactus ( Carnegiea gigantea ) is among the most studied plants in the world. Long‐term studies have shown saguaro establishment to be generally episodic and strongly influenced by precipitation and temperature. Water limitation through lower‐than‐average seasonal rainfall and elevated temperatures increasing evaporative loss can reduce survivorship of recent germinates. Thus, multi‐year, extended drought could cause populations to decline as older saguaros die without replacement. Previous studies have related establishment to temporal variation in rainfall, but most studies have been on non‐randomized plots in ideal habitat and thus might not have captured the full variability within the local area. We studied how saguaro establishment varied in space and which habitat features may buffer responses to drought on 36 4‐ha plots located randomly across an elevation gradient, including substantial replication in landscape position (bajada, foothills, and slopes) in the two disjunct districts of Saguaro National Park in southern Arizona, USA. Recent, severe drought coincided with drastic declines in saguaro establishment across this 25, 000‐ha area. Establishment patterns derived from the park‐wide data set was strongly correlated with drought, but the Park's two districts and diversity of plots demonstrated substantially different population outcomes. Saguaro establishment was best explained by the interaction of drought and habitat type; establishment in bajada and foothill plots dropped to near‐zero under the most severe periods of water limitation but remained higher in slope plots during the same time span. Combined with saguaro density estimates, these data suggest that the most suitable habitat type for saguaro establishment shifted to higher elevations during the time span of the recent drought. These results place into context the extent to which historical patterns of demography provide insight into future population dynamics in a changing climate and reveal the importance of understanding dynamics across the distribution of possible local habitat types with response to variation in weather.